Conversion of labour epidural analgesia to anaesthesia for emergency caesarean section: A retrospective audit - Sunil Thakorbhai Pandya; Jyotsna Mikkilineni; Manokanth Madapu (Wolters Kluwer Medknow Publications, 2021)
Aim: to determine the rates of failed conversion of EA to surgical anaesthesia for patient and clinician information and benchmarking, and to develop an algorithmic approach for safe conversion of EA. Materials and Methods: A retrospective audit of parturients who had labour epidural analgesia (EA) at an advanced tertiary care institute for women and newborn health in south India. Information on EA, caesarean sections, conversion of EA, failure of regional anaesthesia, use of general anaesthesia, alternate techniques and supplemental medications were retrieved from electronic medical records. Results: Emergency cesarean section (CS) was performed for 4,259 (26.93%, 95% CI: 26.25, 27.63) of 15, 812 parturients that had EA at the study institute between Jan 2012 and December 2016. The EA was successful in 4,078 (95.75%, 95% CI: 95.11, 96.32) of these 4,259 women. Seventy three (1.71%, 95% CI: 1.37, 2.15) of the 4,259 women reported mild discomfort on the VAS for pain and required supplemental sedation for the emergency CS and 108 (2.53%, 95% CI: 2.11, 3.05) of the 4,259 women needed alternate techniques. The failure rate of EA was thus 4.25% (95% CI: 3.68, 4.89, n = 181) in this audit. Conclusions: The failure rates of EA at the study institute are well within the recommended standards of the RCA (Royal College of Anaesthesiologists - UK). This audit helped us to develop an algorithmic approach to further improve performance based on problems identified during the audit.